2019
DOI: 10.1177/0897190019850700
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Oxcarbazepine in Pregnant Women With Substance Use Disorders: Focus on Safety

Abstract: Background: Published safety data in pregnant epileptic women suggests that oxcarbazepine (OXC) may be a treatment option in nonepileptic pregnant women with substance use disorders (SUDs) and psychiatric symptomatology. Objective: To compare safety outcomes associated with OXC exposure versus non-exposure in nonepileptic pregnant women with SUD and comorbid psychiatric symptomatology. Methods: A retrospective chart review was conducted to identify pregnant women 18 years or older with a SUD who delivered at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Two studies 32,43 reported an incidence of urogenital malformations following in‐utero exposure to oxcarbazepine. Development of neonatal abstinence syndrome following oxcarbazepine treatment was reported by Johnson et al 42 Various perinatal complications, including C‐section delivery, perinatal death, premature birth, low birth weight, etc., were reported by six studies 30,42 . Learning and language disabilities, developmental disorders and spina bifida were among the major neural outcomes encountered after in‐utero oxcarbazepine exposure 33–36 …”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Two studies 32,43 reported an incidence of urogenital malformations following in‐utero exposure to oxcarbazepine. Development of neonatal abstinence syndrome following oxcarbazepine treatment was reported by Johnson et al 42 Various perinatal complications, including C‐section delivery, perinatal death, premature birth, low birth weight, etc., were reported by six studies 30,42 . Learning and language disabilities, developmental disorders and spina bifida were among the major neural outcomes encountered after in‐utero oxcarbazepine exposure 33–36 …”
Section: Resultsmentioning
confidence: 89%
“…There was no loss of follow-up and confounding factors like maternal age, parity, socioeconomic status, etc., were adjusted in the analysis. A study that included singleton liveborn infants born to women enrolled in the North American Antiepileptic Drug Pregnancy Registry between 1997 and 2016 reported the rate of preterm deliveries in epileptic women who used AEDs to be 9.3%, 51 which was comparable to the risk established by Johnson et al 42 A meta-analysis is only as good as the studies included in it. We devised a comprehensive search strategy, utilized many online databases, and applied no time or location restrictions to ensure selection of the maximum number of articles with information pertaining to our review.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A recent review explored the use of gabapentin and pregabalin in the treatment of patients with BD, indicating a potential role of these medications in the management of SUD comorbidity ( 71 ). Similarly, oxcarbazepine has been proposed as an alternative treatment for SUD during pregnancy ( 72 ), but with scarce evidence for the treatment of SUD in comorbidity with BD ( 73 ). The increased prevalence of polypharmacy, particularly benzodiazepines and other drugs, in patients suffering from BD and polySUD should be framed as an attempt to reduce abstinence, treat residual symptoms as sleep or anxiety derived from potential subsyndromal psychotic symptoms, or recognize the need for better mood stabilization.…”
Section: Discussionmentioning
confidence: 99%